Feeding Effect of Organic and Inorganic Zinc with Vitamin E on Growth Performance and Carcass Quality of Japanese Quail: Efficacy of Organic Zinc with Vitamin E on the Growth of Japanese Quail - Muhammad Akbar Nasar; Nasir Rajput; Azizullah Memon; Athar Mahmud; Shazia Shamas (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2023)
The research facility of Avian Research & Training (ART) Center (Poultry Production), UVAS, Lahore was selected to investigate the effect of feeding organic and inorganic zinc in addition to vit-E on the growth performance of Japanese quail. for a period of 6 months. The diet formulated by the inclusion of ZnO + ZnI (mg)+VE(IU) as 0+0+0 (A), 25+0+0 (B), 0+15+0 (C), 0+0+12 (D), 25+15+0 (E), 25+0+12 (F), 0+15+12 (G) and 25+15+12 (H), respectively. The effect of zinc and vit-E on growth and slaughter traits of Japanese quail was significant (P<0.05) and it was perceived that in 6 weeks the broiler quails in groups H and F took higher feed (745.44 and 734.70 g/bird), with simultaneous effect on LBW of males (175.35 and 174.50 g), females (198.35 and 197.38 g), average (186.85 and 185.94 g), intestine filled (6.81 and 6.66 g) and empty weights (5.51 and 4.88 g), intestine length (44.87 and 44.75 g), cecal length (16.37 and 16.12 cm), the weight of carcass + giblets (142.01 and 141.48 g), carcass (130.88 and 130.25 g), heart (2.18 and 2.16 g), liver (5.02 and 5.06 g), gizzard (5.62 and 5.21 g), respectively. The dietary Zn + vit-E inclusion significantly (P<0.05) increased the relative length of gut segments, villi height, villus thickness, the villi height to crypt depth proportion in jejunum and ileum and the number of goblet cells in various parts of the intestine of quails. The meat production was significantly higher in female quails than the meat of male quails. This suggested that the organic Zn proved to be better than the inorganic Zn source in addition to vit-E to achieve physiology-related traits in quails.